Impact of ‘back to back’ payment clause on the cash flow of subcontractor in the UAE - Bader, Mahmoud Fathi (2013)
Any default by the employer, by not paying on time or nonpaying at all, will adversely affect the parties down in the supply chain in construction project. The contractor tries to cope with such problem by limiting his liability via terms in the contract, such as back-to-back payment terms, with his subcontractors and suppliers. Back to back payment clause has different meanings and forms and its interpretation may vary among the different legal systems. Common law is inclined to invalidate such clause. The situation under the UAE law is different as there is no explicit term in the current law that invalidates the back to back payment clause. The research aimed at investigating the impact of ‘back-to-back’ payment terms on the cash flows of subcontractors and main contractor’s and try to find solutions for securing the subcontractor payments. A total of 96 questionnaire responses were collected from different construction professionals involved in the contract administration or drafting in the UAE. The research asserted that most of the professional participated in the survey felt uncomfortable with back to back payment term. Furthermore, most of the subcontractor participated in the survey have encountered problems due to back to back payment clause Back to back clause has significant impacts in the cash flows of the main contractors and subcontractors. As 65% of the entire professionals participated in the survey claimed so. Furthermore, according to most of the respondents to the survey, back to back clause in unfair term and should be invalidated by the law To conclude, it is worthwhile to the parties to be clear in their contract terms with regards to payment certification and mechanisms. In addition, the legislator should be inspired by the other common laws to adopt payment mechanisms and certainty in the construction industry.